Medial Buttressing in Orbital Blowout Fractures. Issue 5 (September 2018) - Ramesh, Sathyadeepak; Bokman, Christine; Mustak, Hamzah; Lo, Christopher; Goldberg, Robert; Rootman, Daniel
Abstract : Purpose: To study whether ethmoidectomy predisposes the orbit to medial wall fracture with lesser trauma. Methods: An interventional cadaver study of 5 heads (10 orbits); the left or right orbit was randomized to undergo endoscopic complete ethmoidectomy with the fellow orbit as control. Fractures were induced with direct globe trauma, and heads underwent CT scanning. Energy to induce fracture, peak orbital pressure at time of fracture, fracture pattern, and volume of herniated tissue were measured and analyzed. Results: Fractures were induced in both orbits of all cadavers. Experimental orbits after ethmoidectomy sustained orbital fracture at less energy required (2.14 ± 0.66 vs. 3.10 ± 0.19 J, mean difference: −0.96 ± 0.33 J, p < 0.05). Similarly, peak orbital pressure was lower for ethmoidectomized orbits than for controls (11.8 ± 8.42 vs. 28.4 ± 13.2 mm Hg, mean difference: −16.5 ± 6.9 mm Hg, p < 0.05). Orbits after ethmoidectomy were more likely to sustain medial wall involvement in fracture (100%) compared with controls (20%, p < 0.05) and pure medial wall fracture (80%) compared with controls (0%, p < 0.05). Overall volume of herniated orbital contents was not significantly different between groups ( p = 0.25); volume of herniated tissue from the medial wall only was significantly greater in orbits after ethmoidectomy (mean difference: 1.01 ± −0.39 cm, 3 p < 0.05). Conclusion: Endoscopic ethmoidectomy in fresh cadavers reduces impact energy necessary to induce orbital fracture and increases the prevalence of medial wall involvement. Clinicians may wish to counsel patients undergoing endoscopic sinus surgery about these relative risks. Abstract : Endoscopic ethmoidectomy in fresh cadavers is shown to increase the prevalence of medial wall involvement and decreases impact energy required to induce orbital blowout fracture.